IMPLEMENTASI KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KOTA MAKASSAR - Ahmad Syawal; Muhlis Madani; Nuryanti Mustari (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2021)
ABSTRACT The present study aims to understand and analyze implementation of sustainable food agriculture land protection policies in Makassar city. This study uses qualitative method through case-study approach, and uses observation instruments, interviews and documentation to collect data. Informants were selected by purposive sampling, which is furthermore analyzed by data reduction, data presentation, and drawing conclusion. The result obtained from this research figures out that Makassar city government does not have a Regional Regulation (PERDA), that organize spatial planing of Makassar city (RTRW) regarding the protection of sustainable agricultural food land in Makassar City. Meanwhile, there is Regional Regulation number 4 of 2015 concerning regional spatial planning of Makassar city which explains that there is an area in Makassar for agricultural area, as regulate in article 72 paragraph (2) that some of the Biringkanaya sub-districts with an area 168,79 hectares is only as a planed or as a cultivated agricultural area which is still in the planning stage, and can be transferred or managed to other things later. The Makassar city government is still in the process of ownership of agricultural land in Makassar city, and is still in the stage of budgeting and formulating a plan to procure a sustainable agricultural food protection area in Makassar City which will be included in the preparation of the new Makassar City regional regulations.Keywords: Policy, Land conservation, Agriculture